Purification of the carbon dioxide emitted by gas treatment plants - Gámez, Nancy; Cobo, Martha (Universidad Pedagógica y Tecnológica de Colombia, 2018)
In natural gas plants, the carbon dioxide (CO2) traveling in the extracted stream is separated and released to the atmosphere. This stream also contains hydrogen sulfide (H2S), water and hydrocarbons. The purpose of this investigation was to design a process to purify this CO2 stream, to its further use in the food industry. There, the CO2 can be employed in carbonated drinks and as supercritical fluid; requiring a purity higher than 99.95 mol%. Therefore, a real flow of 3454 ton/year CO2 was selected as case of study, which is emitted in a gas treatment plant located in Neiva, Colombia. This stream was simulated in ProMax and subjected to chemical absorption with methyl diethanolamine (MDEA), to a dehydration with diethylene glycol combined with molécular sieve, to a Ryan-Holmes cryogenic process for removing light components (methane and ethane) and their combinations. The combination of the three processes allowed us for a 99.95% CO2 recovery and a 99.99 mol% CO2 purity, requiring capital expenses (CAPEX) of USD 412.323 or 53 USD/tCO2. This CO2 could be commercialized at sell prices as high as 5000 USD/tCO2 to the food industry. In addition, the combination of the two first processes delivered a CAPEX of 37 USD/tCO2 with a 99.85 mol% CO2 purity, suitable for other applications requiring less purity in the food industry or improved oil recovery.